Comparative chloroplast genomics of Cypripedioideae: structural divergence, adaptive evolution, and phylogenomic insights - Zhao, Xiaoyan; Lan, Xiaoxiao; Wang, Zishuo; Li, Dong; Sun, Wei; Gai, Yunpeng; Liu, Bing (Frontiers in Plant Science, 2026)
The Cypripedioideae subfamily (slipper orchids) exhibits remarkable ecological diversity, spanning temperate to tropical habitats, yet the molecular mechanisms underlying its adaptive radiation remain poorly understood. Chloroplast genomes, with their critical roles in photosynthesis and conserved structure, offer a powerful system to investigate how evolutionary forces shape genomic adaptation. This study presents the most comprehensive analysis to date of codon usage bias (CUB) and structural evolution in Cypripedioideae chloroplast genomes, evaluating the relative contributions of mutational pressure and natural selection across ecologically divergent lineages. We assembled and annotated the complete chloroplast genome of Paphiopedilum armeniacum and integrated it with 47 publicly available genomes, representing all four genera of Cypripedioideae. Comparative analyses included genome structure relative synonymous codon usage (RSCU), effective number of codons (ENC) vs. GC3s plots, neutrality analysis, parity rule 2 (PR2) bias analysis, simple sequence repeat (SSR) profiling, and selection pressure assessment (Ka/Ks). Phylogenetic reconstruction was performed using maximum likelihood based on 81 concatenated protein-coding genes. Cypripedioideae chloroplast genomes displayed substantial size variation (147–230 kb) and lineage-specific structural features, including inverted repeat (IR) expansion and small single-copy (SSC) contraction in Paphiopedilum. Codon usage was strongly biased toward A/U-ending codons, with minimal influence from mutational pressure. ENC-GC3s plots, neutrality analysis (regression slopes = 0.003–0.324), and PR2 plots consistently indicated that natural selection accounted for >90% of CUB variation across most species. Ka/Ks analysis revealed predominant purifying selection (94.7% of genes with Ka/Ks < 1), with photosystem and ribosomal protein genes under the strongest constraints. Phylogenomic analysis resolved genus-level relationships and showed correlations between genome architecture, codon usage patterns, and ecological distributions. Our findings demonstrate that natural selection, rather than mutational pressure, is the primary driver of codon usage optimization in Cypripedioideae chloroplast genomes. Lineage-specific structural variations—including IR/SSC boundary dynamics, genome size expansion, and ndh gene loss—are closely associated with ecological adaptations to temperate, subtropical, and tropical environments. This study provides novel insights into the interplay between selection-driven codon usage, plastome structural evolution, and ecological diversification, offering a genomic framework for understanding adaptive evolution in orchids and other plant lineages.